THE EFFECT OF AUGMENTED REALITY (AR) MEDIA ON THE ABILITY OF HOTS IPAS IN CLASS V STUDENTS OF SDN GERIH 1: - Tasya Dian Lestari; Miratu Chaeroh; Aulia Fajar Khasanah (SOSIOEDUKASI, 2026)
The low ability of Higher Order Thinking Skills (HOTS) students in science subjects, especially natural disasters that affect environmental change, shows the need for innovation in more interactive learning media. The use of conventional methods causes students to be less optimal in understanding concepts and solving hots-based problems. Augmented Reality (AR) learning Media is seen to be able to visualize concepts concretely and interactively so that it has the potential to improve students ' high-level thinking skills. This study aims to determine the effect of Augmented Reality (AR) learning media on the ability of HOTS students in Grade V of SDN Gerih 1. The research uses quantitative approach with quasi experiment method and non-equivalent control group design. The research sample consisted of 35 fifth grade students consisting of experimental class at Sdn Gerih 1 and control class at SDN Keraskulon 1. Data were collected through pretest and posttest hots test, then analyzed using normality test, homogeneity, Paired Sample T-Test, and SPSS-assisted Independent Sample T-Test. The results showed that learning media Augmented Reality (AR) significantly affect the ability of HOTS students. The average value of the experimental class increased from 63.75 to 77.25, while the control class from 48.67 to 46.00. The test results showed a significance value of 0.000 < 0.05, so that Augmented Reality (AR) learning media is effective in improving the ability of HOTS students in science subjects